Advanced fibre optic long period grating sensors; design, fabrication and sensing - Wong, Rebecca (Cranfield University, 2014)
This thesis describes the process and technique used to fabricate reproducible optical fibre long period gratings (LPG) of various types. It explores how they can be exploited for use as highly selective and sensitive sensors. A versatile method for fabricating LPG sensors has been demonstrated. The single system has the capability of fabricating LPGs of different configurations, such as uniform period, those operating at the phase matching turning point (PMTP), as well as phase shifted and chirped. LPGs were characterised for their sensitivities to temperature, axial strain and surrounding refractive index. The gratings at the PMTP were found to show higher sensitivities to external influences. Novel sensing configurations that exploit the properties of LPGs were also constructed. An LPG coated with a molecularly imprinted ceramic coating was demonstrated to offer a selective method for porphyrin detection. A composite nanoscale of a titanium oxide (TiO2) matrix and 5, 10, 15, 20 Tetrakis-(N-methyl-piridinium4- yl)-21H, 23H-porphine tertakis (p-toluenesulfonate) [TMPyP] porphyrin template film was deposited on the LPG via liquid phase deposition. Attempts to rebind porphyrins to the matrix were carried out. The LPGs transmission spectrum exhibited a higher sensitivity to the target TMPyP template than it did to other, structurally similar porphyrins, showing high selectivity. A continuously chirped long period grating (CCLPG) sensor for monitoring directional flow and cure of an epoxy resin is also presented. The asymmetric properties of the CCLPG were exploited to facilitate the measurement of the direction of the flow. The CCLPG was also used to monitor changes in the refractive index of the resin during its cure, showing close agreement with a fibre optic Fresnel refractometer.